Representação gráfica de feições lineares do relevo: proposta de aplicação de simbologia linear digital na cartografia geomorfológica - Souza, Luiz Humberto de Freitas (2006)
The discussion about the quality of the cartographical documents has been kept for decades, and a lot of theoretical and technical impasses have been observed. Questioned from a side the methods of symbol representation and from the other side, the means utilized for getting the graphical result of symbol representation, occur almost all the time a convergence for the problems of standardization of the cartographical works. Since the last half of the 20th century, the geomorphology students, in national and international scope, discuss these facts directing it to the geomorphological cartography. The more common laments discussed are always oriented to absence or deficiency of the professional qualification and the inexistence or no compromising with the normalization of the cartographical standards, specifically the symbols representation. Nowadays, these discussions add to the blunder of cartographic production linked to the informatics advances. It is known the negligence about the use of the cartographical techniques and, at the same time, people are living now with easy methods for elaboration and utilization of the digital bases, which permit the dissemination of the new signs, which becomes the standardization to slow. Based in this fact, occur an inevitable necessity of develop new methods for using alternative software which permit the creation of digital symbol library for being available to the geomorphology cartographical professionals, optimizing the work and propitiating the map standardization. So, the mainly objectify of this research is the use of AutoCAD software to develop and improvement of special lines for utilization in the geomorphology cartographical, allowing the continuation of the studies done by Souza (2003), which were used as a final work course at UFU. The theoretical part of this study is based in the technical manual proposed by the ITC (1975), which shows some geomorphology and geology basic conventions. Through an analytic and comparative study of this material, and using the recourse of the CAD system allied to the applications, will be developed linear symbols representatives of the more common geomorphological surfaces.